The cultural politics of European prostitution reform: governing loose women - Mattson, Greggor (Palgrave Macmillan, 2016)
Governing loose women : the new politics of prostitution -- States of anxiety : prostitution reform as a symptom of European integration -- Dutch pragmatism and the difficulties of professionalizing prostitution -- Legislating peace for women : Sweden's sex purchase act -- German consensus for sex work, compromise over sex business -- Finland on the fence : abolitionist compromise at the edge of Europe -- Seeing transnational problems through national lenses -- The truly trafficked woman, and other globalization anxieties -- Methodological afterword : identity work and the interviewer